Time in Context - Harry, Chelsea C. (Chronos in Aristotle’s Physics: On the Nature of Time, 2015)
The key to taking in Aristotle’s treatise on time is to approach it with the understanding that Aristotle was not a philosopher concerned with time —in questions about time or in delimiting the being of time.
Citation Key Alias: lens.org/039-932-676-491-061
Keywords: Accidental Change; Accidental Form; Natural Object; Predicative Change; Privative Form; dept.phi

Physics iv 10-11 as a Parallel Account - Harry, Chelsea C. (Chronos in Aristotle’s Physics: On the Nature of Time, 2015)
Given the context of the Physics just explored, it will not be a surprise if time (chrόnos) in Aristotle’s analytic of time turns out to be not a being qua itself but an attribute of motion, an interval.
Citation Key Alias: lens.org/010-220-856-100-488
Keywords: Infinite Divisibility; Infinite Time; Internal Inconsistency; Natural Object; Underlying Unity; dept.phi

Has εὐβίοτος in Aristotle’s Historia Animalium ix Been Mistranslated? - Harry, Chelsea (Journal of Ancient Philosophy, 2025)
Le terme εὐβίοτος, « bien vivre », et ses équivalents apparaissent dans les observations d'Aristote sur les oiseaux, dans l'Historia Animalium IX. Cette note de recherche compare la façon dont le terme aristotélicien a été traduit dans les manuscrits grecs, latins et arabes, ainsi que dans les traductions modernes et contemporaines en anglais, français et allemand, et démontre qu'il a été mal traduit, à commencer par les traducteurs humanistes du XVe siècle, Georges de Trébizonde et Théodore Gaza. Les libertés prises dans la surinterprétation du terme aristotélicien ont peut-être obscurci ce qu'il cherchait à communiquer sur les capacités des oiseaux.
Keywords: Art; Epistemology; Literature; Philosophy; dept.phi

Schelling & Plato - Harry, Chelsea (Palgrave handbooks in German idealism, 2026)
Keywords: Dialectic; Mythology; Natural (archaeology); Opposition (politics); Reflexive pronoun; dept.phi

Situating the early schelling in the later positive philosophy - Harry, Chelsea C (Comparative and Continental Philosophy, 2014)
This is a translation of the second chapter of F.W.J. Schelling's Abhandlungen zur Erlaüterung des Idealismus der Wissenschaftslehre (1796-1797). It is preceded by a brief introduction in which I situate the chapter within Schelling's oeuvre and suggest that it is not only an early articulation of Schellingian Naturphilosophie, but also prescient, anticipating Schelling's later positive philosophy. © W. S. Maney & Son Ltd 2014.
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/113-953-556-691-16X tex.type: [object Object]
Keywords: Naturphilosophie; Negative philosophy; Positive philosophy; Schelling; dept.phi

Nature, Ethics and Gender in German Romanticism and Idealism - Harry, Chelsea C. (Idealistic Studies, 2020)
0 citations (Crossref) [2023-10-31] WOS:000541068700006
Keywords: dept.phi; peer-reviewed

Chronos in Aristotle's Physics: On the Nature of Time - Harry, Chelsea C. (Springer, 2015)
Keywords: Aristotle. Physics; Time; Philosophy; Philosophy of nature; Philosophy; Physics; dept.phi; faculty_collection

Introduction: Schelling and the Environment - Harry, Chelsea C. (Environment, Space, Place, 2022)
0 citations (Crossref) [2023-10-31]
Keywords: dept.phi

Sappho of Lesbos and the Time of Erosophy - Harry, Chelsea C (Routledge Handbook on Women and Ancient Greek Philosophy, 2024)
Keywords: dept.phi

New Sappho as a Philosopher of Time? - Harry, Chelsea C (Women in the History of Philosophy and Sciences, 2023)
Keywords: dept.phi

Schelling and Plato - Harry, Chelsea C (Palgrave Schelling Handbook, 2023)
Keywords: dept.phi

On the Perception of Time in Ancient Greece - Harry, Chelsea C (In Anderen Zeiten/In Other Times: Zeitdiskurse im Wandel/ Changing Discourses of Time across Human History, 2022)
Keywords: dept.phi

Plato on Women’s Natural Ability: Revisiting Republic V and Timaeus 41e3–44d2 and 86b1–92c3 - Harry, Chelsea; Ron, Polansky (Apeiron, 2016)
Abstract Despite the prominent argument for equal educational opportunity for women in Republic V, commentators frequently question Plato’s sincerity, the quality of the case made, or its significance. Undermining confidence in Plato’s advocacy of female equality are derogatory remarks about women in this and other dialogues. Since we take Plato to be sincere in the argument in Republic V, we reconcile his conclusions there about the equal educational opportunity for women with these seemingly problematic remarks by suggesting that the remarks reflect the interlocutors involved in the dialogue and conventional Athenian prejudices of that time rather than ideas that Plato held to be true. We take seriously the observation of Levin 1996, 14, “in none of those passages in which Plato makes derogatory remarks about women does he use phusis to explain why they behave in the ways of which he is critical.” Hence Plato never suggested that women were by nature limited to the position they occupied socially and politically in 5th or 4th century Athens; he understood the difference between the way they were by convention and the way that they could be, in accordance with their nature, were they to develop their natural capacities through education. We examine carefully Plato’s argument for the equal nature of women in Republic V to defend its viability. The provocation is our not finding in the extensive secondary literature a really detailed treatment of the actual argument and appreciation that it is intended as a sound philosophical argument. We then turn to the devolution schemes in Timaeus 41e–44d and 86b–92c, which again touch on the nature of women and appear to counter the position we attribute to Plato, to show that they are really supportive of our account. Both the Republic and Timaeus limit the natural differences between males and females to body-type. Therefore, even relative physical weakness of women’s bodies does not much problematize for Plato that their natural abilities are equal to those of men, where nature in these contexts means suitability to perform certain functions.
Keywords: dept.phi

Brill's Companion to the Reception of Presocratic Natural Philosophy in Later Classical Thought - Harry, Chelsea C; Habash, Justin (Brill, 2021)
Keywords: Ancient Philosophy; Classical Studies; Classical Tradition & Reception Studies; History; History of Science; Philosophy; Philosophy of Science; dept.phi

Exploring the Contributions of Women in the History of Philosophy, Science, and Literature, Throughout Time - Harry, Chelsea C.; Vlahakis, George N. (Springer, 2023)
This book explores contributions by some of the most influential women in the history of philosophy, science, and literature
Keywords: dept.phi